Synergy of Omeprazole and Praziquantel In Vitro Treatment against Schistosoma mansoni Adult Worms. - Giulliana T Almeida; Regina C G Lage; Leticia Anderson; Thiago M Venancio; Helder I Nakaya; Patrícia A Miyasato; Henrique K Rofatto; Adhemar Zerlotini; Eliana Nakano; Guilherme Oliveira; Sergio Verjovski-Almeida (Public Library of Science (PLoS), 2015)
Treatment and morbidity control of schistosomiasis relies on a single drug, praziquantel (PZQ), and the selection of resistant worms under repeated treatment is a concern. Therefore, there is a pressing need to understand the molecular effects of PZQ on schistosomes and to investigate alternative or synergistic drugs against schistosomiasis.We used a custom-designed Schistosoma mansoni expression microarray to explore the effects of sublethal doses of PZQ on large-scale gene expression of adult paired males and females and unpaired mature females. We also assessed the efficacy of PZQ, omeprazole (OMP) or their combination against S. mansoni adult worms with a survival in vitro assay.We identified sets of genes that were affected by PZQ in paired and unpaired mature females, however with opposite gene expression patterns (up-regulated in paired and down-regulated in unpaired mature females), indicating that PZQ effects are heavily influenced by the mating status. We also identified genes that were similarly affected by PZQ in males and females. Functional analyses of gene interaction networks were performed with parasite genes that were differentially expressed upon PZQ treatment, searching for proteins encoded by these genes whose human homologs are targets of different drugs used for other diseases. Based on these results, OMP, a widely prescribed proton pump inhibitor known to target the ATP1A2 gene product, was chosen and tested. Sublethal doses of PZQ combined with OMP significantly increased worm mortality in vitro when compared with PZQ or OMP alone, thus evidencing a synergistic effect.Functional analysis of gene interaction networks is an important approach that can point to possible novel synergistic drug candidates. We demonstrated the potential of this strategy by showing that PZQ in combination with OMP displayed increased efficiency against S. mansoni adult worms in vitro when compared with either drug alone.